Obesity Increases In-Hospital Mortality of Acute Type A Aortic Dissection Patients Undergoing Open Surgical Repair: A Retrospective Study in the Chinese Population - Pan, Xiaogao; Xing, Zhenhua; Yang, Guifang; Ding, Ning; Zhou, Yang; Chai, Xiangping (Frontiers in Cardiovascular Medicine, 2022)
Objective: The prevalence of obesity is increasing worldwide, and the role of the obesity paradox in cardiovascular surgery remains controversial. Here, we redefined obesity according to Chinese criteria, and examined the relationship between obesity and in-hospital mortality in acute type A aortic dissection (AAD) undergoing open surgical repair. Methods: 289 AAD patients (between 2014 and 2016) were divided into non-obese group and obese group for correlation analysis, general information, demographic factors, blood biochemistry, surgical details, complications were used as covariates. Survival was estimated by the Kaplan–Meier method, and any differences in survival were evaluated with a stratified log-rank test. Least Absolute Shrinkage and Selection Operator (LASSO) regression and logistic regression were used to evaluate the effect and interaction of obesity on surgical mortality. Results: The 289 patients had a mean age of 48.64 (IQR 44.00-55.00) and male of 74.39%, of whom 228 were non-obesity (78.89%) and 61 were obesity (21.11%). Patients with obesity were younger and more prone to unstable blood pressure (SBP and DBP), preoperative hypoxemia and delirium, prolonged operative time, and surgical wound deep infection(P<0.05). In the fully adjusted model, we observed an increased risk of in-hospital mortality in obese patients after fine-tuning other covariates including age and sex (HR=2.65; 95%CI=1.03 to 6.80; P=0.042). The interaction suggested that obesity was more likely to cause death in elderly patients (age ≥ 60), although it was more common in younger patients (test for interaction, P=0.012). Conclusion: Obesity, interacting with age, increases the risk of in-hospital mortality in AAD patients undergoing open surgical repair. Although more verification is needed, we believe these findings provide further evidence for the treatment of AAD.